2015
DOI: 10.3389/fnins.2015.00150
|View full text |Cite
|
Sign up to set email alerts
|

Hippocampal developmental vulnerability to methylmercury extends into prepubescence

Abstract: The developing brain is sensitive to environmental toxicants such as methylmercury (MeHg), to which humans are exposed via contaminated seafood. Prenatal exposure in children is associated with learning, memory and IQ deficits, which can result from hippocampal dysfunction. To explore underlying mechanisms, we have used the postnatal day (P7) rat to model the third trimester of human gestation. We previously showed that a single low exposure (0.6 μg/gbw) that approaches human exposure reduced hippocampal neuro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
19
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(19 citation statements)
references
References 57 publications
(116 reference statements)
0
19
0
Order By: Relevance
“…Alternatively, the loss of cells in medial pallium and optic tectum may also be related to an inhibition of cell proliferation promoted by MeHg, as previously hypothesized in D. sargus exposed to iHg (Pereira et al, 2016) and as observed in the hippocampus and cerebellum of rats exposed to MeHg (Burke et al, 2006;Falluel-Morel et al, 2007;Sokolowski et al, 2013;Obiorah et al, 2015). Studies with MeHg have indicated that the decreased number of brain cells in mammals is a result of the inhibition of proliferation rather than cell death (Lewandowski et al, 2003 and references herein).…”
Section: Mehg-induced Brain Morphometric Alterationsmentioning
confidence: 59%
See 2 more Smart Citations
“…Alternatively, the loss of cells in medial pallium and optic tectum may also be related to an inhibition of cell proliferation promoted by MeHg, as previously hypothesized in D. sargus exposed to iHg (Pereira et al, 2016) and as observed in the hippocampus and cerebellum of rats exposed to MeHg (Burke et al, 2006;Falluel-Morel et al, 2007;Sokolowski et al, 2013;Obiorah et al, 2015). Studies with MeHg have indicated that the decreased number of brain cells in mammals is a result of the inhibition of proliferation rather than cell death (Lewandowski et al, 2003 and references herein).…”
Section: Mehg-induced Brain Morphometric Alterationsmentioning
confidence: 59%
“…Such evidence is in line with several studies in rodents (Nagashima, 1997) and humans (Sanfeliu et al, 2001;Ceccatelli et al, 2010) that have described the occurrence of neuronal damage upon MeHg exposure. In order to unveil the neurotoxic effects of MeHg, rodent brain has been scrutinized by stereological methods comprising an evaluation of cell numbers and volumes (Sager et al, 1984;Larsen and Braendgaard, 1995;Roegge et al, 2006;Falluel-Morel et al, 2007;Sokolowski et al, 2013;Obiorah et al, 2015). This methodology has provided clarification about the localized effects of MeHg in the nervous system of rodents.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Ki-67 and DCX-ir cells were quantified in 6 corresponding sections/ per animal (approximately 250 μm apart) containing the dentate gyrus following a method modified from Obiorah et al (2015). The first section was situated at a level corresponding to sagittal level 12 (lateral 1.725 mm) of Allen's reference atlas of the mouse brain (Dong, 2008) and the rest were placed medial to the first one.…”
Section: Sub Granular Zone Of the Dentate Gyrusmentioning
confidence: 99%
“…Although it is well known that prenatal exposure to MeHg induces abnormal brain development, recent study shows that MeHg vulnerability declines with age, and that early exposure impairs later neurogenesis in older juveniles [29]. Interestingly, in vitro study also showed that co-culture of astrocytes with neurons was less vulnerable to MeHg assaults than neuron alone.…”
Section: Discussionmentioning
confidence: 98%